Biomass solid fuel
By molding and heating biomass powder to create a fuel with controlled volatile content and adhesion, the self-heating and water resistance issues of biomass fuels are addressed, resulting in a stable and efficient solid fuel for storage and handling.
Patent Information
- Application Number
- JP2019546693
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-10-04
- Filing Date
- 2018-10-01
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2038-10-01
AI Technical Summary
Existing biomass solid fuels face issues with self-heating properties, making them difficult to handle and store, and they often disintegrate when exposed to water, leading to increased oxygen demand and COD in wastewater.
A biomass solid fuel is produced by molding biomass powder into unheated lumps and heating them, maintaining connection or adhesion between powders, with a maximum temperature below 200°C in self-heating tests, and utilizing specific volatile content and fuel ratios to enhance water resistance and reduce COD.
The resulting fuel is easy to transport and store, maintains structural integrity in water, and reduces COD in wastewater, while avoiding self-heating and maintaining desirable handling properties.
Smart Images

Figure 0007617706000006 
Figure 0007617706000007 
Figure 0007617706000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a biomass solid fuel. [Background technology]
[0002] Conventionally, solid fuels made by molding woody biomass have been known, but they are difficult to handle because they disintegrate due to rainwater during outdoor storage, and organic matter such as tar dissolves, increasing the COD (chemical oxygen demand) of wastewater. Patent Document 1 describes a method for obtaining solid fuel that does not use binders, does not disintegrate due to rainwater during storage, prevents tar dissolution, and reduces the COD of wastewater by performing molding and heating after steam explosion of plant-based raw materials. Patent Document 2 also describes a biomass solid fuel that reduces the COD in wastewater and also reduces pulverization. The biomass solid fuel described in Patent Document 2 is obtained by molding biomass into unheated agglomerates and heating them, but this method does not include a steam explosion step, so that cost increases can be suppressed compared to the method for producing biomass solid fuel described in Patent Document 1. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2014 / 087949 [Patent Document 2] International Publication No. 2016 / 056608 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the self-heating property of the solid fuel was not sufficiently examined in Patent Documents 1 and 2. Therefore, an object of the present invention is to provide a biomass solid fuel that has low self-heating property and is easy to transport and store. [Means for solving the problem]
[0005] One aspect of the present invention relates to the following.
[0006] 1. The connection or adhesion between the biomass powders is maintained, A biomass solid fuel that has a maximum temperature of less than 200°C in a self-heating test based on the United Nations Recommendations on the Transport of Dangerous Goods: Manual of Tests and Criteria: 5th Edition: Self-heating test.
[0007] 2. The biomass solid fuel according to item 1 above, wherein the solid fuel has a volatile matter content on an anhydrous ash-free basis of 65.0 to 95.0 wt % and a fuel ratio of 0.10 to 0.45.
[0008] 3. The biomass solid fuel described in 1 or 2 above, in which the connection or adhesion between the biomass powder particles is maintained after immersion in water.
[0009] 4. Biomass solid fuel, wherein the raw material of the biomass powder comprises rubber wood, and the volatile matter content of the biomass solid fuel on an anhydrous ash-free basis is 74.0 wt% or more, and the fuel ratio is 0.37 or less; A biomass solid fuel, the raw material of the biomass powder containing acacia, the biomass solid fuel having a dry ash-free volatile content of 77.5 wt% or more and a fuel ratio of 0.285 or less; a biomass solid fuel, the raw material of the biomass powder containing a species of Dipterocarpaceae, the biomass solid fuel having a dry ash-free volatile matter content of 77.2 wt% or more and a fuel ratio of 0.295 or less; A biomass solid fuel, the raw material of the biomass powder containing radiata pine, the biomass solid fuel having a dry ash-free volatile content of 77.5 wt% or more and a fuel ratio of 0.295 or less; A biomass solid fuel, the raw material of the biomass powder comprising a mixture of larch, spruce and birch, the biomass solid fuel having a dry ash-free volatile content of 71.0 wt% or more and a fuel ratio of 0.405 or less; or The raw material of the biomass powder includes a mixture of spruce, pine, and fir, and the biomass solid fuel has a dry ash-free volatile content of 74.3 wt% or more and a fuel ratio of 0.34 or less. 4. The biomass solid fuel according to any one of 1 to 3 above.
[0010] 5. A biomass solid fuel according to any one of 1 to 4 above, which is obtained by molding biomass powder into unheated lumps and heating the unheated lumps. Effect of the Invention
[0011] According to the present invention, it is possible to provide a biomass solid fuel that has low self-heating properties and is easy to transport and store, and a method for producing the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 13 is a diagram showing the relationship between the solid temperature of a solid fuel and the maximum temperature reached in a self-heating test. [Diagram 2] FIG. 1 is a graph showing the relationship between the solid temperature of a solid fuel and the BET specific surface area. [Figure 3A] FIG. 13 is a graph showing the relationship between the solid temperature of the solid fuel and the concentration of the generated O2 gas in the generated gas analysis. [Figure 3B] FIG. 13 is a graph showing the relationship between the solid temperature of the solid fuel and the concentration of generated CO gas in the generated gas analysis. [Figure 3C] FIG. 13 is a diagram showing the relationship between the solid temperature of the solid fuel and the concentration of the generated CO2 gas in the generated gas analysis. [Figure 4] FIG. 1 is a diagram showing a (presumed) mechanism for the development of solid cross-links in PBT. [Diagram 5] FIG. 2 shows the results of FT-IR analysis of the outer surface of a solid fuel pellet. [Figure 6] FIG. 1 shows the results of FT-IR analysis of the center of a cross section of a solid fuel pellet. [Figure 7] FIG. 13 is a diagram showing the results of FT-IR analysis of an acetone extract of a solid fuel. [Figure 8] FIG. 1 shows the results of FT-IR analysis of the solid after acetone extraction of the solid fuel. [Figure 9] FIG. 1 shows the results of GC-MS analysis of an acetone extract of a solid fuel. [Figure 10] FIG. 13 is a diagram showing the shape of pellets after immersing solid fuel in saline. [Figure 11] FIG. 13 shows the distribution of sodium before and after immersion of a solid fuel in saline. [Figure 12] FIG. 1 shows the TG of solid fuel. [Figure 13] FIG. 1 shows a DTA of a solid fuel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] One embodiment of the biomass solid fuel of the present invention is a biomass solid fuel formed from raw biomass powder, in which the connection or adhesion between the biomass powder particles is maintained, and the maximum temperature reached in a self-heating test based on the "United Nations Recommendations on the Transport of Dangerous Goods: Manual of Tests and Criteria: 5th Edition: Self-heating test" is less than 200°C, making it an easy solid fuel to transport and store.
[0014] The solid fuel of the present invention uses a heated solid obtained through a molding process in which biomass is crushed and pulverized, and the biomass powder in a chip or powder form is compressed and molded into a lump, and a heating process in which the lump after the molding process is heated (corresponding to PBT described later). The biomass solid fuel of the present invention has a low maximum temperature of less than 200°C in a self-heating test and preferable properties (e.g., water resistance, grindability) by adjusting, for example, the species of biomass used as a raw material, the heating temperature in the heating process (sometimes referred to as "solid temperature" in this specification), and the like. The proximate analysis value, elemental analysis value, and higher heating value in this specification are based on JIS M 8812, 8813, and 8814. In this specification, the raw material biomass is also simply referred to as "raw material" or "biomass", the lump obtained in the molding process and before the heating process is also referred to as "unheated lump", and the obtained biomass solid fuel is also simply referred to as "solid fuel".
[0015] In one embodiment of the biomass solid fuel of the present invention, for example, its anhydrous ashless (also referred to as "daf") volatile content is preferably 65.0 wt% or more, more preferably 68.0 wt% or more, and even more preferably 70.0 wt% or more, and the upper limit is lower than the anhydrous ashless volatile content of unheated solid fuel (unheated lump, corresponding to WP described below) molded from the same raw material biomass powder, for example, 95 wt% or less, preferably 88 wt% or less. As shown in the examples described below, the inventor of the present invention found that there is a correlation between the temperature rise due to self-heating of the solid fuel and the amount of anhydrous ashless volatile content of the solid fuel. That is, by adjusting the amount of anhydrous ashless volatile content of the solid fuel, the maximum temperature reached in the self-heating test can be suppressed to less than 200°C.
[0016] In one embodiment of the biomass solid fuel of the present invention, for example, the fuel ratio (fixed carbon / volatile matter) is preferably 0.45 or less, more preferably 0.42 or less, and even more preferably 0.40 or less. The lower limit is higher than the fuel ratio of unheated solid fuel (unheated lump, corresponding to WP described below) molded from biomass powder of the same raw material, and is, for example, 0.10 or more.
[0017] In one embodiment of the biomass solid fuel of the present invention, for example, its higher heating value on an anhydrous basis is preferably 4500 to 7000 (kcal / kg), more preferably 4500 to 6000 (kcal / kg).
[0018] In one embodiment of the biomass solid fuel of the present invention, for example, the molar ratio of oxygen O to carbon C (O / C) is preferably 0.440 to 0.700, more preferably 0.440 to 0.650, more preferably 0.500 to 0.650, and even more preferably 0.500 to 0.600. The molar ratio of hydrogen H to carbon C (H / C) is preferably 1.100 to 1.350.
[0019] The biomass solid fuel of the present invention preferably has a COD (chemical oxygen demand) of 3000 mg / L or less, more preferably 1000 mg / L or less, of the soaking water when soaked in water. Here, the COD (chemical oxygen demand) of the soaking water when the biomass solid fuel is soaked in water (also simply referred to as "COD") refers to the COD value obtained by preparing a soaking water sample for COD measurement according to the test method for metals, etc. contained in industrial waste, Environment Agency Notification No. 13 (a) of 1973, and analyzing the sample according to JIS K0102 (2010)-17.
[0020] The biomass solid fuel obtained after the heating step is not particularly limited, but preferably has a crushability index (HGI) based on JIS M 8801 of 15 to 70, more preferably 20 to 60. In addition, the BET specific surface area is preferably 0.10 m 2 / g~0.80m 2 / g, and preferably 0.11m 2 / g~0.80m 2 More preferably, it is 0.15m 2 / g~0.80m 2 / g. Furthermore, in the biomass solid fuel of the present invention, the connection or adhesion between the biomass powders is maintained even after immersion in water, and the equilibrium moisture after immersion in water is preferably 10 to 65 wt%, more preferably 15 to 65 wt%, even more preferably 15 to 50 wt%, and even more preferably 15 to 45 wt%. When the physical property values of the biomass solid fuel are within the above ranges, it is possible to reduce the COD in wastewater during storage while also reducing powdering, and to improve the handleability during storage.
[0021] The raw material of the biomass solid fuel of the present invention is not particularly limited, but in one embodiment, it is preferable that the raw material contains at least one biomass selected from the group consisting of rubber tree; acacia; dipterocarpaceae tree species; radiata pine; a mixture of larch, spruce, and birch; and a mixture of spruce, pine, and fir. Larch, spruce, and birch may each be used alone as the raw material biomass, but it is preferable to use a mixture of two or more, preferably three, of these. Also, spruce, pine, and fir may each be used alone as the raw material biomass, but it is preferable to use a mixture of two or more, preferably three, of these. The biomass solid fuel of the present invention does not require a steam explosion step or a binder in its production method, so that it is possible to suppress cost increases.
[0022] The raw material may further contain other tree species other than those mentioned above. In one aspect of the present invention, the content of one or more biomasses selected from the group consisting of rubber tree, acacia, dipterocarpaceae tree species, radiata pine, a mixture of larch, spruce, and birch, and a mixture of spruce, pine, and fir, relative to the total weight of the raw material biomass, is preferably 50% by weight or more, more preferably 80% by weight or more, and may be 100% by weight.
[0023] The particle size of the biomass powder is not particularly limited, but is preferably about 100 μm to 3000 μm on average, more preferably 400 μm to 1000 μm on average. The particle size of the biomass powder may be measured by a known measurement method. As described later, in the biomass solid fuel (PBT) of the present invention, the connection or adhesion between the biomass powders is maintained by solid cross-linking, so the particle size of the biomass powders is not particularly limited as long as it is within a moldable range. In addition, since fine pulverization is a cost increase factor, the particle size may be within a known range as long as it is within a range that allows both cost and moldability to be achieved.
[0024] As described above, the biomass solid fuel of the present invention is produced by a method including a molding step and a subsequent heating step. In the molding step, the biomass solid fuel is shaped into lumps using a known molding technique. The lumps are preferably pellets or briquettes and may be of any size. In the heating step, the shaped lumps are heated in an atmosphere with an oxygen concentration of 10% or less.
[0025] The method for producing a biomass solid fuel of the present invention includes a molding step of molding biomass powder of crushed and pulverized biomass to obtain unheated aggregates, and a heating step of heating the unheated aggregates to obtain a heated solid, and the heating temperature in the heating step is preferably 170° C. to 400° C. This heating temperature is appropriately determined depending on the shape and size of the raw biomass and aggregates, and is preferably 170 to 400° C., more preferably 200 to 350° C., even more preferably 230 to 300° C., and particularly preferably 230 to 280° C. The heating time in the heating step is not particularly limited, but is preferably 0.2 to 3 hours.
[0026] If the bulk density of the unheated aggregates before the heating step is A and the bulk density of the heated solid after the heating step is B, then B / A=0.6-1 is preferable. The value of the bulk density A is not particularly limited as long as it is within a known range in which the biomass powder can be molded to obtain an unheated aggregate. The bulk density may be appropriately set depending on the type of raw biomass. The bulk density can be measured by the method described in the examples below. If the HGI (Hardgrove Crushability Index of JIS M8801) of the unheated aggregates is H1 and the HGI of the heated solid is H2, then H2 / H1 (HGI ratio) is preferably 1.1-4.0, more preferably 1.1-2.5. By heating so that either or both of the values of B / A (bulk density ratio) and H2 / H1 (HGI ratio) are within this range, it is possible to obtain a biomass solid fuel that reduces COD in wastewater during storage while reducing pulverization and improving handleability during storage.
[0027] [Type of raw biomass and properties of solid fuel] The properties of the biomass solid fuel may be determined in a suitable range depending on the species of biomass used as a raw material. Preferred ranges for the types of biomass raw materials, the properties of the resulting solid fuel, and the production method thereof are described below, but these are merely examples and the present invention is not limited to these.
[0028] (Rubber wood: solid fuel a) As one embodiment of the present invention, the properties of the biomass solid fuel (hereinafter, sometimes referred to as solid fuel A) in which the raw material contains rubber wood are as follows: The rubber wood content in the raw material of solid fuel A is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%.
[0029] The maximum temperature reached in the self-heating test for solid fuel a based on the "United Nations: Recommendations on the Transport of Dangerous Goods: Manual of Tests and Criteria: 5th Edition: Self-heating test" (also referred to simply as the "self-heating test" in this specification) is less than 200°C.
[0030] The volatile content of the solid fuel a on an anhydrous ashless basis is preferably 74.0 wt% or more, more preferably 75.0 wt% or more, even more preferably 76.0 wt% or more, and even more preferably more than 80.1 wt%. Also, it is preferably less than 83.0 wt%. By having the volatile content on an anhydrous ashless basis within this range, it is easy to obtain a solid fuel a with reduced self-heating properties.
[0031] The BET specific surface area is 0.350m 2 / g~0.442m 2 It is preferred that the molecular weight is / g.
[0032] The HGI is preferably from 20 to 34, and more preferably from 25 to 33. The HGI ratio is preferably from 1.1 to 2.5, and more preferably from 1.5 to 2.0.
[0033] The fuel ratio is preferably 0.37 or less, more preferably 0.365 or less, more preferably 0.34 or less, and even more preferably 0.32 or less. There is no particular lower limit, but it is preferably more than 0.21, and more preferably 0.25 or more.
[0034] The higher heating value on an anhydrous basis is preferably 4650 to 5180 kcal / kg, more preferably 4700 to 5150 kcal / kg, even more preferably 4750 to 5050 kcal / kg, and even more preferably 4885 kcal / kg or more.
[0035] The molar ratio O / C of oxygen O to carbon C is preferably from 0.50 to 0.65, and more preferably from 0.50 to 0.60.
[0036] The molar ratio H / C of hydrogen H to carbon C is preferably 1.145 to 1.230, more preferably 1.145 to 1.220. When O / C and H / C are within the above ranges, it is easy to obtain a solid fuel a whose maximum temperature in a self-heating test is less than 200°C.
[0037] The solid yield (see the Examples below for the calculation method, the same applies below) is preferably 77 wt% or more, more preferably 80 wt% or more, even more preferably 83 wt% or more, and even more preferably 88 wt% or more. The upper limit is not particularly limited, but is preferably 95 wt% or less.
[0038] The preferable ranges for the properties of the solid fuel a have been described above.
[0039] In addition, when producing the solid fuel a, the heating temperature in the heating step is not particularly limited, but is preferably 170°C to 254°C, more preferably 200°C to 254°C, and further preferably 225°C to 254°C.
[0040] (Acacia: Solid fuel b) As one embodiment of the present invention, the properties of a biomass solid fuel (hereinafter, sometimes referred to as solid fuel b) in which the raw material contains acacia are as follows: The content of acacia in the raw material of solid fuel b is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%.
[0041] The maximum temperature reached in the self-heating test of solid fuel b is less than 200°C.
[0042] The volatile content of the solid fuel b on an anhydrous ashless basis is preferably 77.5 wt% or more, more preferably 77.8 wt% or more, and even more preferably 78.0 wt% or more. Also, it is preferably less than 83.1 wt%. By having the volatile content on an anhydrous ashless basis within this range, it is easy to obtain a solid fuel b with reduced self-heating properties.
[0043] The HGI is preferably from 25 to 60, and more preferably from 35 to 55. The HGI ratio is preferably from 1.35 to 3.5, and more preferably from 1.5 to 3.2.
[0044] BET specific surface area is 0.250m 2 / g~0.500m 2 / g, and preferably 0.300m 2 / g~0.480m 2 More preferably, it is 0.350m 2 / g~0.450m 2 It is more preferable that the molecular weight is / g.
[0045] The fuel ratio is preferably equal to or less than 0.285, more preferably equal to or less than 0.280, and more preferably greater than 0.20.
[0046] The higher calorific value on an anhydrous basis is preferably from 4800 to 5260 kcal / kg, more preferably from 4900 to 5260 kcal / kg, and even more preferably from 4900 to 5250 kcal / kg.
[0047] The molar ratio O / C of oxygen O to carbon C is preferably from 0.52 to 0.62, and more preferably from 0.52 to 0.60. The molar ratio H / C of hydrogen H to carbon C is preferably from 1.205 to 1.300, and more preferably from 1.205 to 1.290.
[0048] The solid yield is preferably 84.0 wt% or more, more preferably 84.5 wt% or more, and further preferably 85.0 wt% or more. There is no particular upper limit, but it is preferably 95 wt% or less.
[0049] The preferable ranges for the properties of the solid fuel b have been described above.
[0050] In addition, when producing the solid fuel b, the heating temperature in the heating step is not particularly limited, but is preferably 170 to 252°C, more preferably 200 to 252°C, and further preferably 225 to 252°C.
[0051] (Dipterocarpaceae: Solid fuel c) In one embodiment of the present invention, the properties of biomass solid fuel (hereinafter, sometimes referred to as solid fuel c) in the case where the raw material contains a tree species of the Dipterocarpaceae family are as follows. The content of Dipterocarpaceae in the raw material of solid fuel c is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%. Examples of tree species of the Dipterocarpaceae family include Selangorium serrata, Meranti, Kruin, and Kapur. The solid fuel c may further contain biomass of a family other than Dipterocarpaceae as a raw material. The biomass of a family other than Dipterocarpaceae is not particularly limited, but is preferably a tropical broadleaf tree such as a Leguminosae family tree such as Scepter or Merbau, or a Malvaceae family tree such as Scaphium.
[0052] The maximum temperature reached in the self-heating test of solid fuel c is less than 200°C.
[0053] The dry ashless volatile content of the solid fuel c is preferably 77.2 wt% or more, more preferably 77.5 wt% or more, even more preferably 78.0 wt% or more, and even more preferably 78.5 wt% or more. Also, it is preferably less than 84.4 wt%. By having the dry ashless volatile content within this range, it is easy to obtain a solid fuel c with reduced self-heating properties.
[0054] The HGI is preferably from 25 to 60, and more preferably from 30 to 60. The HGI ratio is preferably from 1.05 to 3.0, and more preferably from 1.2 to 3.0.
[0055] BET specific surface area is 0.250~0.400m 2 / g, and 0.300 to 0.400m 2 It is more preferable that the molecular weight is / g.
[0056] The fuel ratio is preferably equal to or less than 0.295, more preferably equal to or less than 0.29, and even more preferably equal to or less than 0.28. Also, it is preferably greater than 0.18.
[0057] The higher calorific value on an anhydrous basis is preferably from 4800 to 5300 kcal / kg, more preferably from 4900 to 5300 kcal / kg, and even more preferably from 4950 to 5270 kcal / kg.
[0058] The molar ratio O / C of oxygen O to carbon C is preferably from 0.515 to 0.620, more preferably from 0.520 to 0.620, and further preferably from 0.545 to 0.620.
[0059] The molar ratio H / C of hydrogen H to carbon C is preferably 1.21 to 1.30.
[0060] The solid yield is preferably 84.5 wt% or more, more preferably 85.0 wt% or more, even more preferably 85.5 wt% or more, and even more preferably 87.8 wt% or more. The upper limit is not particularly limited, but is preferably 95 wt% or less.
[0061] The preferable ranges for the properties of the solid fuel c have been described above.
[0062] In addition, when producing the solid fuel c, the heating temperature in the heating step is not particularly limited, but is preferably 170 to 259°C, more preferably 200 to 259°C, and further preferably 225 to 259°C.
[0063] (Radiata pine: solid fuel d) In one embodiment of the present invention, the properties of a biomass solid fuel (hereinafter sometimes referred to as solid fuel d) containing radiata pine as a raw material are as follows: The content of radiata pine in the raw material of solid fuel d is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%.
[0064] The maximum temperature reached in the self-heating test of solid fuel d is less than 200°C.
[0065] The volatile content of the solid fuel d on an anhydrous ashless basis is preferably 77.5 wt% or more, more preferably 77.8 wt% or more, and even more preferably 78.0 wt% or more. Also, it is preferably less than 87.2 wt%. By having the volatile content on an anhydrous ashless basis within this range, it is easy to obtain a solid fuel d with reduced self-heating properties.
[0066] The BET specific surface area is 0.250m 2 / g~0.350m 2 / g is preferred, and 0.250m 2 / g~0.333m 2 More preferably, it is 0.250m 2 / g~0.330m 2 It is more preferable that the molecular weight is / g.
[0067] The HGI is preferably from 25 to 45, and more preferably from 30 to 40. The HGI ratio is preferably from 1.01 to 2.0, and more preferably from 1.2 to 1.7.
[0068] The fuel ratio is preferably equal to or less than 0.295, more preferably equal to or less than 0.290, and even more preferably equal to or less than 0.285. Also, it is preferable that the fuel ratio is more than 0.15.
[0069] The higher calorific value on an anhydrous basis is preferably from 4800 to 5440 kcal / kg, more preferably from 4900 to 5440 kcal / kg, and even more preferably from 5000 to 5440 kcal / kg.
[0070] The molar ratio O / C of oxygen O to carbon C is preferably from 0.505 to 0.650, and more preferably from 0.505 to 0.600. The molar ratio H / C of hydrogen H to carbon C is preferably from 1.18 to 1.35, and more preferably from 1.18 to 1.30.
[0071] The solid yield is preferably 80.0 wt% or more, more preferably 80.5 wt% or more, and further preferably 81.0 wt% or more. There is no particular upper limit, but it is preferably 95 wt% or less.
[0072] The above describes the preferable ranges for the properties of the solid fuel d.
[0073] In addition, when producing the solid fuel d, the heating temperature in the heating step is not particularly limited, but is preferably 170 to 274°C, more preferably 200 to 274°C, and further preferably 230 to 274°C.
[0074] (Mixture of larch, spruce and birch: solid fuel e) As one embodiment of the present invention, the properties of a biomass solid fuel (hereinafter, sometimes referred to as solid fuel e) in which the raw material contains a mixture of larch, spruce, and birch are as follows. The mixing ratio of larch, spruce, and birch is not particularly limited, but may be, for example, larch:spruce:birch=30-70:25-65:0-25 by weight. The content of the mixture of larch, spruce, and birch in the raw material of solid fuel e is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%.
[0075] The maximum temperature reached in self-heating tests for solid fuel e is less than 200°C.
[0076] The volatile content of the solid fuel e on an anhydrous ashless basis is preferably 71.0 wt% or more, more preferably 73.0 wt% or more, and even more preferably 76.0 wt% or more. Also, it is preferably less than 85.9 wt%. By having the volatile content on an anhydrous ashless basis within this range, it is easy to obtain a solid fuel e with reduced self-heating properties.
[0077] The BET specific surface area is 0.120m 2 / g~0.250m 2 / g, and preferably 0.150m 2 / g~0.250m 2 More preferably, it is 0.150m 2 / g~0.230m 2 More preferably, it is 0.155 m 2 / g~0.230m 2 Even more preferably, it is / g.
[0078] The HGI is preferably from 18 to 40, and more preferably from 20 to 35. The HGI ratio is preferably from 1.01 to 2.5, and more preferably from 1.15 to 2.2.
[0079] The fuel ratio is preferably equal to or less than 0.405, more preferably equal to or less than 0.35, and even more preferably equal to or less than 0.30. Also, it is preferable that the fuel ratio is greater than 0.16.
[0080] The higher calorific value on an anhydrous basis is preferably 4800 to 5700 kcal / kg, more preferably 4800 to 5600 kcal / kg, and even more preferably 4900 to 5500 kcal / kg.
[0081] The molar ratio O / C of oxygen O to carbon C is preferably 0.44 to 0.64, and more preferably 0.50 to 0.63. The molar ratio H / C of hydrogen H to carbon C is preferably 1.10 to 1.30.
[0082] The solid yield is preferably 71.0 wt% or more, more preferably 75.0 wt% or more, and further preferably 78.0 wt% or more. There is no particular upper limit, but it is preferably 95 wt% or less.
[0083] The above describes the preferred ranges for the properties of solid fuel e.
[0084] In addition, when producing the solid fuel e, the heating temperature in the heating step is not particularly limited, but is preferably 170 to 289°C, more preferably 200 to 285°C, and further preferably 220 to 280°C.
[0085] (Mixture of spruce, pine and fir: solid fuel f) In one embodiment of the present invention, the properties of biomass solid fuel (hereinafter, sometimes referred to as solid fuel f) in which the raw material contains a mixture of spruce, pine, and fir are as follows. The mixture ratio of spruce, pine, and fir is not particularly limited, but may be, for example, spruce:pine:fir=20-40:30-60:10-40 by weight. The content of the mixture of spruce, pine, and fir in the raw material of solid fuel f is preferably 50 wt% or more, more preferably 70 wt% or more, even more preferably 80 wt% or more, and may be 100 wt%.
[0086] The maximum temperature reached in the self-heating test of solid fuel f is less than 200°C.
[0087] The volatile content of the solid fuel f on an anhydrous ashless basis is preferably 74.3 wt% or more, more preferably 74.5 wt% or more, and even more preferably 75.0 wt% or more. It is also preferably less than 85.6 wt%, and more preferably 85.0 wt% or less. By having the volatile content on an anhydrous ashless basis within this range, it is easy to obtain a solid fuel f with reduced self-heating properties.
[0088] The BET specific surface area is 0.200m 2 / g~0.317m 2 / g, and 0.230m 2 / g~0.317m 2 It is more preferable that the molecular weight is / g.
[0089] The HGI is preferably from 19 to 39, and more preferably from 20 to 38. The HGI ratio is preferably from 1.20 to 2.20, and more preferably from 1.50 to 2.10.
[0090] The fuel ratio is preferably equal to or less than 0.34, more preferably equal to or less than 0.33, and more preferably greater than 0.17, more preferably equal to or greater than 0.18.
[0091] The higher calorific value on an anhydrous basis is preferably 4800 to 5560 kcal / kg, more preferably 4800 to 5550 kcal / kg, and further preferably 4900 to 5500 kcal / kg.
[0092] The molar ratio O / C of oxygen O to carbon C is preferably from more than 0.47 to 0.61, and more preferably from 0.48 to 0.60. The molar ratio H / C of hydrogen H to carbon C is preferably from more than 1.10 to 1.26, and more preferably from 1.11 to 1.25.
[0093] The solid yield is preferably 75.5 wt% or more, more preferably 76.0 wt% or more, and even more preferably 76.5 wt% or more. There is no particular upper limit, but it is preferably 95 wt% or less.
[0094] The preferable ranges for the properties of the solid fuel f have been described above.
[0095] In addition, when producing the solid fuel f, the heating temperature in the heating step is not particularly limited, but is preferably from 170 to less than 280°C, more preferably from 200 to 279°C, and even more preferably from 220 to 279°C.
[0096] As described above, the biomass solid fuel of the present invention is a biomass solid fuel that has low self-heating properties, is easy to transport and store, and has good properties as a fuel.
[0097] The present inventors have speculated that in the method for producing biomass solid fuel, by performing a molding step followed by a heating step in which the unheated aggregates are heated, the connection or adhesion between the biomass powders is maintained using components derived from the raw material biomass without using a binder, and a highly water-resistant biomass solid fuel that does not collapse even when immersed in water can be produced. Through analysis by the present inventors, the following findings have been obtained regarding the mechanism by which biomass solid fuel acquires water resistance.
[0098] The present inventors performed FT-IR analysis, GC-MS analysis, SEM observation, etc. on three types of biomass solid fuels produced by different manufacturing methods, specifically, an unheated solid fuel obtained by molding pulverized biomass (White Pellet: sometimes referred to as "WP"), and a solid fuel obtained by molding pulverized biomass and then heating (Pelletizing Before Torrefaction: sometimes referred to as "PBT"), and analyzed the mechanism of water resistance of the biomass solid fuel. Note that no binder is used in either WP or PBT. Figures 5 to 8 show an example of the results of FT-IR analysis of the biomass solid fuel, and Figure 9 shows the results of GC-MS analysis of an acetone extract of the biomass solid fuel (see Examples for details).
[0099] First, the acetone extracts of each solid fuel were analyzed by FT-IR. It was found that the PBT obtained through the heating process had a lower content of hydrophilic COOH groups compared to unheated WP, but a higher content of C=C bonds, suggesting that heating changes the chemical structure of the components that make up the biomass, making them hydrophobic.
[0100] Furthermore, GC-MS analysis of the acetone-extracted components of each solid fuel suggested that the thermal decomposition of terpenes such as abietic acid and its derivatives (hereafter referred to as "abietic acid, etc.") by heating is involved in the water resistance of biomass solid fuels. Abietic acid, etc., is the main component of rosin contained in pine and other trees.
[0101] FIG. 4 is a diagram showing the mechanism (estimate) of solid cross-linking development in PBT. In the case of PBT, in the heating process after the molding process, as the temperature rises, the liquid resulting from the melting of abietic acid dissolves into the gaps between the pulverized biomass (also described as "biomass powder") (the gaps between adjacent biomass powders that are compressed by molding after crushing), and further evaporation and thermal decomposition of abietic acid occurs, and hydrophobic substances are fixed to the gaps between the above-mentioned biomass powders, developing cross-links (solid cross-links). As a result, the connection or adhesion between the biomass powders is maintained by the abietic acid derived from the raw material biomass without adding a binder. It is therefore considered that the biomass powders are connected or bonded to each other, suppressing the intrusion of water, and improving water resistance.
[0102] On the other hand, in the case of WP, biomass powder is simply molded without being heated, so there is no solid cross-linking between the biomass powder particles as in the case of PBT. As mentioned above, the surface of the raw biomass powder that makes up WP contains many hydrophilic COOH groups, etc., so water can easily penetrate, and the penetrated water greatly widens the gaps between the biomass powder particles, making the molded pellets etc. more likely to collapse.
[0103] Also, in the case of solid fuel molded after heating biomass powder (Pelletizing After Torrefaction: hereafter sometimes referred to as PAT), the surface of each individual biomass powder becomes hydrophobic due to the elution of abietic acid etc. by heating, but because it is crushed and molded only after it has become hydrophobic by heating, it is thought that cross-linking between the biomass powders does not occur as in PBT. Therefore, with PAT, which is heated before molding, water easily seeps into the gaps between the compacted biomass powders, and it is presumed that the water resistance is inferior to PBT.
[0104] Abietic acid or its derivatives have a melting point of about 139 to 142° C. and a boiling point of about 250° C. Therefore, it is presumed that when heated, abietic acid, etc. melts near the melting point, causing liquid crosslinking, and abietic acid, etc. pyrolyzes near the boiling point, causing solid crosslinking.
[0105] Terpenes such as abietic acid are generally contained in biomass (Hokkaido Prefectural Forest Products Research Institute Monthly Report No. 171, April 1966, Japan Wood Preservation Association, Wood Preservation, Vol. 34-2 (2008), etc.). Although the content varies slightly depending on the type of biomass (Utilization of Essential Oils, Tatsuro Ohira, Japan Wood Research Society, 6th Research Subcommittee Report, p. 72, Table 1, Japan Wood Research Society, 1999, etc.), in the following examples, water resistance (not disintegrating even after immersion in water, see Table 2) is observed when heated to 230°C or higher, so it is considered that water resistance is imparted to biomass in general by heating at least 230°C to 250°C or higher.
[0106] Furthermore, with PBT, the strength of the solid fuel is improved due to the development of solid cross-linking, and it is presumed that, like water resistance, good crushability (HGI, ball mill crushability) and good handleability (mechanical durability, powdering test) can be obtained without adding a binder by heating to at least 230°C to 250°C. Furthermore, as mentioned above, PBT reduces COD, and this is thought to be because heating causes the tar components of the biomass raw material to volatilize, while at the same time the surface of the PBT solid fuel is covered with solidified abietic acid, etc., which further makes the solid fuel surface hydrophobic and suppresses the elution of the tar components remaining in the biomass raw material.
[0107] As shown in Fig. 1 and in the Examples described later, the higher the heating temperature (also referred to as "solid temperature" or "target temperature") in the heating step during the production of biomass solid fuel (PBT), the higher the maximum temperature reached in the self-heating test tends to be. The present inventors have conducted detailed studies on the relationship between the solid temperature and self-heating, and have obtained the following findings.
[0108] As the solid temperature of the solid fuel increases, the BET specific surface area of the solid fuel increases (Figure 2). This is thought to be because as the solid temperature increases, the thermal decomposition of the solid fuel progresses, the content of volatile matter decreases, and pores develop on the surface of the solid fuel, making it porous. A detailed study of the gas generated from each solid fuel showed that the O2 concentration in the generated gas decreases as the solid temperature increases, indicating that the amount of O2 adsorbed on the surface of the solid fuel increases (Figure 3A). On the other hand, as the solid temperature increases, the CO and CO2 concentrations increase, suggesting that an oxidation reaction (exothermic reaction) is progressing due to the adsorbed O2 (Figures 3B and 3C). Figures 1 to 3C show the analysis results when rubber wood was used as the raw material, but similar results were obtained when radiata pine was used as the raw material (see the examples below for details).
[0109] From these results, the following reaction mechanism is considered for the relationship between the solid temperature of solid fuel and self-heating. First, when the heating temperature during production of solid fuel rises, thermal decomposition progresses in the solid fuel, reducing the volatile content, making the pellet surface porous and increasing the BET specific surface area. This increases the amount of O2 adsorbed onto the surface of the solid fuel, and the oxidation reaction (exothermic reaction) progresses. Therefore, it is presumed that when the solid temperature exceeds a certain point, the amount of heat stored exceeds the amount of heat released, and the maximum temperature reached in the self-heating test exceeds 200°C. EXAMPLES
[0110] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.
[0111] The abbreviations used in this specification are as follows. FC: fixed carbon VM: Volatile HHV: Higher heating value on an anhydrous basis HGI: Hardgrove Crushability Index AD: Air-dried base daf: dry ash-free basis dry: on an anhydrous basis
[0112] The analytical methods for each biomass solid fuel used in the examples are described below.
[0113] <Before immersion in water> [yield] The solid yield is the weight ratio before and after heating (100 x dry weight after heating / dry weight before heating (%)), and the heat yield is the ratio of the heat release before and after heating (higher heating value after heating (anhydrous basis) x solid yield / higher heating value before heating (anhydrous basis)). As described later, the target temperature (heating temperature) of each example was not maintained.
[0114] Furthermore, the fuel ratio calculated based on the higher heating value (anhydrous basis), proximate analysis value (air-dry basis), and the elemental analysis value (anhydrous basis) and the molar ratios of oxygen (O), carbon (C), and hydrogen (H) obtained based on the results were calculated. As mentioned above, the HGI is based on JIS M 8801, and the higher the value, the better the grindability. The HGI ratio is calculated by HGI after heating / HGI before heating. In Tables 1A, 1B, and 3A described below, "HHV" is the higher heating value (anhydrous basis), "FC" is the fixed carbon (air-dry basis), "VM" is the volatile matter (AD is air-dry basis, daf is anhydrous ash-free basis), and the fuel ratio is the value calculated by "FC(AD) / VM(AD)".
[0115] [BET specific surface area] For each solid fuel, the BET specific surface area was measured using an automatic specific surface area / pore size distribution measuring device (BELSORP-min II, manufactured by BEL Japan Co., Ltd.) by cutting the sample into pieces of 2 to 6 mm as pretreatment and filling a container, followed by vacuum degassing at 100°C for 2 hours. Nitrogen gas was used as the adsorption gas.
[0116] [Ball mill grindability] The grinding time for each biomass solid fuel was set to 20 minutes, and the weight ratio of the 150μm sieve after 20 minutes was taken as the grinding point. The ball mill used was one conforming to JIS M4002, and a cylindrical container with an inner diameter of 305mm and axial length of 305mm was filled with standard ball bearings (Φ36.5mm x 43 pieces, Φ30.2mm x 67 pieces, Φ24.4mm x 10 pieces, Φ19.1mm x 71 pieces, Φ15.9mm x 94 pieces) specified in JIS B1501 was rotated at a speed of 70 rpm for measurement. A higher value indicates improved grindability.
[0117] [Dimensions before immersion (diameter and length)] For each solid fuel, the pellet length (L1 (mm)) and pellet diameter (φ1 (mm)) were measured before immersion in water. For pellet length, 10 pellets were randomly selected for each solid fuel before immersion and measured using an electronic caliper (Mitutoyo: CD-15CX, repeatability of 0.01 mm, rounded off to two decimal places). If the pellet end was oblique, the length was measured up to the very tip. The pellet diameter was also measured using the same electronic caliper. The measured pellet length and diameter are the average values of 10 pellets.
[0118] [Solid strength before immersion in water (mechanical durability)] For each solid fuel, the mechanical durability DU was measured in accordance with the American Agricultural Standard ASAE S 269.4 and the German Industrial Standard DIN EN 15210-1 based on the following formula, where m0 is the sample weight before the rolling process, m1 is the sample weight on the sieve after the rolling process, and the sieve used was a plate sieve with a circular hole diameter of 3.15 mm.
[0119] DU = (m1 / m0) x 100
[0120] [Bulk density] For each solid fuel, the bulk density BD was calculated according to the British national standard BS EN15103:2009 using the following formula: BD=(m2-m1) / V The measurement was performed using a container with an inner diameter of 167 mm and a height of 228 mm. In the formula, m1 is the container weight, m2 is the container weight + sample weight, and V is the container volume.
[0121] <After immersion in water> The methods for measuring the COD of the immersion water when solid fuel is immersed in water, and the methods for measuring the diameter, length, pH, solid moisture content, and mechanical durability of solid fuel after it is immersed in water for 168 hours are as follows.
[0122] [COD] The COD (chemical oxygen demand) of the soaking water was measured when each biomass solid fuel was soaked in water. The preparation of the soaking water sample for COD measurement was in accordance with the Environment Agency Notification No. 13 (a) of 1973, which stipulates the method for testing metals, etc. contained in industrial waste, and the COD was analyzed according to JIS K0102 (2010)-17.
[0123] [Dimensions after immersion in water (diameter and length)] After immersion in water, the pellet length (L2 (mm)) and pellet diameter (φ2 (mm)) of each solid fuel were measured in the same way as before immersion. The pellet length was measured using an electronic caliper (Mitutoyo: CD-15CX, repeatability was 0.01 mm, rounded off to two decimal places) for 10 randomly selected pellets before immersion. If the pellet end was oblique, the length was measured up to the very tip. The pellet diameter was also measured using the same electronic caliper. The measured pellet length and diameter are the average values of 10 pellets.
[0124] [pH] Each solid fuel was immersed in water at a solid-liquid ratio of 1:3, and the pH was measured.
[0125] [Solid water content after immersion in water] The solid fuel of each example was immersed in water, and after 168 hours, it was taken out and the moisture on the solid surface was wiped off with a cloth to measure the solid moisture content. 100 x (weight of solid after immersion in water - dry weight of solid after immersion in water) / weight of solid after immersion in water The calculation was made as follows.
[0126] [Mechanical durability after immersion in water] The mechanical durability of the pellets of each example after immersion in water for 168 hours was measured in the same manner as before immersion in water.
[0127] [Self-heating] The evaluation was based on the "United Nations: Recommendations on the Transport of Dangerous Goods: Manual of Tests and Criteria: 5th Edition: Self-heating test." A sample container (a stainless steel cube with sides of 10 cm) was filled with biomass solid fuel and suspended inside a thermostatic chamber. The temperature of the material was measured continuously for 24 hours at a temperature of 140°C, and the highest temperature was recorded as the "maximum reached temperature." Materials that were recognized to ignite or reach a temperature of 200°C or higher were recognized as self-heating materials.
[0128] In the following Examples a to f, biomass solid fuels were produced by the following production methods. In all the Examples and Comparative Examples, no binder was used in the production of the biomass solid fuel. The properties of these solid fuels are shown in Tables 1A, 1B, 2, 3A, and 3B.
[0129] <Example a: Rubber tree> In the following Examples a1 to a5 and Comparative Examples a1 to a3, rubber trees were used as the raw biomass material to produce biomass solid fuels as described below.
[0130] (Example a1~A5, Comparative example a2~a3) Biomass was crushed and pulverized, and the crushed biomass was molded in a molding process and a subsequent heating process to obtain a biomass solid fuel (PBT). No binder was used in any of the processes. In the molding process of each example, the biomass was molded into a pellet shape with a diameter of 7.5 mm. In the heating process of each example, 4 kg of each raw material (molded biomass) was put into a φ600 mm electric batch furnace, and the temperature was raised to the target temperature in each example (heating temperature in Table 1A) at a heating rate of 2°C / min, and the furnace was heated with nitrogen purging at an oxygen concentration of 5% or less. Hereinafter, the target temperature and the heating temperature refer to the same thing. In all of Examples a1 to a5, Comparative Example a2, and Comparative Example a3, the target temperature (heating temperature) was not maintained (the same applies to Examples b to f below). The heating temperatures in the heating processes of Examples a1 to a5, Comparative Example a2, and Comparative Example a3, and the properties of the biomass solid fuel obtained after the heating process are shown in Tables 1A and 2. In addition, since the moisture content after immersion in water is after 168 hours of immersion, it is considered that the moisture content in the solid fuel has essentially reached equilibrium.
[0131] (Comparative Example a1) Comparative Example a1 is an unheated biomass solid fuel (WP) that was only crushed, pulverized, and then molded, without undergoing a heating process. No binder was used in Comparative Example a1 either. The properties of the solid fuel of Comparative Example a1 are also shown in Tables 1A and 2. After immersion in water for 168 hours, the pellets of the unheated biomass solid fuel (WP) of Comparative Example a1 collapsed, and it was not possible to measure the properties.
[0132] The solid fuels (PBT) of Comparative Examples a2 and a3 had a maximum temperature of 200°C or higher in the self-heating test. In contrast, the solid fuels of Examples a1 to a5 had a low maximum temperature in the self-heating test, indicating that they were easy to transport and store. The results of Tables 1A and 2 indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature in the self-heating test.
[0133] Comparative Example a1 (WP: biomass solid fuel that was molded but not heated) was unable to maintain its pellet shape and collapsed when immersed in water (168 hours) as described above. In contrast, the solid fuels of Examples a1 to a5 maintained the connections or adhesion between the biomass powders and did not collapse when immersed in water. The COD of the wastewater discharged when stored outdoors was low, and these solid fuels showed advantageous properties as solid fuels that are often stored outdoors.
[0134] The HGI (based on JIS M 8801) of ordinary coal (bituminous coal) is around 50, but the properties of the solid fuels of Examples a1 to a5 change when heated, and the HGI (based on JIS M 8801) values are higher than that of Comparative Example a1 (WP). The HGI of ordinary coal (bituminous coal) is around 50, and the crushing characteristics of Examples a1 to a5 can be said to be closer to that of coal and better than Comparative Example a1.
[0135] Regarding mechanical durability (DU), the strength of Examples a1 to a5 (PBT) that had undergone the heating process was hardly reduced, and it was shown that they were less likely to pulverize and could maintain their handleability compared to Comparative Example a1 (WP) before immersion in water and the corresponding PBT before immersion in water. Note that the mechanical durability of the solid fuel of Comparative Example a1 could not be measured because it disintegrated when immersed in water.
[0136] The pH after immersion in water was generally around 6, indicating that there is no particular problem with the pH of the wastewater discharged during outdoor storage.
[0137] From the results of ball mill grindability, it was confirmed that the grinding point was good.
[0138] These results are believed to be due to the surface of the biomass solid fuel becoming hydrophobic due to the elution and solidification of organic components such as tar caused by heating, and show advantageous characteristics as a solid fuel that is often stored outdoors. In addition, since the solid fuel is in pellet form, it is mainly compacted in the radial direction, and therefore it is believed that the expansion is also large in the radial direction (the same is true for examples b to f).
[0139] <Example b: Acacia> In Examples b1 to b3 (PBT) and Comparative Examples b2 to b4 (PBT), biomass solid fuel was produced in the same manner as Example a1, except that acacia was used as the raw biomass, which was molded into pellets with a diameter of 8 mm in the molding process and heated to the heating temperature listed in Table 1A. The properties of the biomass solid fuel (Examples b1 to b3, Comparative Examples b2 to b4) obtained after the heating process were measured by the above-mentioned method. In Comparative Example b1 (WP), the properties were measured using the same raw materials as Examples b1 to b3 and Comparative Examples b2 to b4, except that the heating process was not performed. Since the moisture after immersion in water is after immersion for 168 hours, it is considered that the moisture in the solid fuel has substantially reached equilibrium. In Comparative Example b1, the pellets collapsed immediately after immersion in water, and it was not possible to measure each property. The results are shown in Tables 1A and 2.
[0140] In Comparative Examples b2 to b4 (PBT), the maximum temperature reached in the self-heating test was 200°C. In contrast, the solid fuels of Examples b1 to b3 had a low maximum temperature reached in the self-heating test, indicating ease of transportation and storage. The results in Tables 1A and 2 indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature reached in the self-heating test.
[0141] Comparative Example b1 (WP) was unable to maintain its pellet shape and collapsed after immersion in water (168 hours) as described above. In contrast, the solid fuels of Examples b1 to b3 did not collapse when immersed in water, maintained the connections or adhesion between the biomass powders, and exhibited advantageous properties as solid fuels that are often stored outdoors, with low COD of the wastewater discharged when stored outdoors.
[0142] Furthermore, the solid fuels of Examples b1 to b3 were also excellent in physical properties such as HGI, mechanical durability (DU), pH after immersion in water, and ball mill crushability.
[0143] <Example c: Dipterocarpaceae> In examples c1 to c4 and comparative example c2 (PBT), biomass mainly containing Dipterocarpaceae species (55 wt% Selangorium serrata, 24 wt% Kruin, 4 wt% Scepter, 9 wt% Scaphium, 8 wt% other tropical broadleaf trees, each wt% indicates the ratio to the total weight of biomass) was used as a raw material, molded into pellets with a diameter of 8 mm, and heated to the heating temperature listed in Table 1A. Except for this, biomass solid fuel was produced in the same manner as in example a1. The properties of the biomass solid fuel (examples c1 to c4, comparative example c2) obtained after the heating step were measured by the above-mentioned method. In comparative example c1 (WP), the properties were measured using the same raw material as in examples c1 to c4 and comparative example c2, except that the heating step was not performed. Since the moisture after immersion in water is after immersion for 168 hours, it is considered that the moisture in the solid fuel has substantially reached equilibrium. In Comparative Example c1, the pellets immediately disintegrated after immersion in water, and it was not possible to measure the properties. The results are shown in Tables 1A and 2.
[0144] The maximum temperature reached in the self-heating test for Comparative Example c2 (PBT) was 200°C. In contrast, the solid fuels of Examples c1 to c4 had low maximum temperatures reached in the self-heating test, indicating ease of transportation and storage. The results in Tables 1A and 2 indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature reached in the self-heating test.
[0145] Comparative Example c1 (WP) was unable to maintain its pellet shape and collapsed after immersion in water (168 hours) as described above. In contrast, the solid fuels of Examples c1 to c4 did not collapse when immersed in water, maintained the connections or adhesion between the biomass powders, and exhibited advantageous properties as solid fuels that are often stored outdoors, with low COD in the wastewater discharged when stored outdoors.
[0146] Furthermore, the solid fuels of Examples c1 to c4 were also excellent in physical properties such as HGI, mechanical durability (DU), pH after immersion in water, and ball mill crushability.
[0147] <Example d: Radiata pine> In Examples d1 to d4 and Comparative Example d2 (PBT), radiata pine was used as the raw biomass, and the raw biomass was molded into pellets with a diameter of 6 mm in the molding process, and the temperature was increased to the heating temperature listed in Table 1B. The properties of the biomass solid fuel (Examples d1 to d4, Comparative Example d2) obtained after the heating process were measured by the above-mentioned method. In Comparative Example d1 (WP), the raw materials were used similarly to Examples d1 to d4 and Comparative Example d2, except that the heating process was not performed, and the properties were measured. Since the moisture content after immersion in water is after immersion for 168 hours, it is considered that the moisture content in the solid fuel has substantially reached equilibrium. In Comparative Example d1, the pellets collapsed immediately after immersion in water, and it was not possible to measure each property. The results are shown in Tables 1B and 2.
[0148] The maximum temperature reached in the self-heating test for Comparative Example d2 (PBT) was 200°C. In contrast, the maximum temperatures reached in the self-heating test for the solid fuels of Examples d1 to d4 were low, indicating ease of transportation and storage. The results of Tables 1B and 2 indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature reached in the self-heating test.
[0149] Comparative Example d1 (WP) was unable to maintain its pellet shape and collapsed after immersion in water (168 hours) as described above. In contrast, the solid fuels of Examples d1 to d4 did not collapse when immersed in water, maintained the connections or adhesion between the biomass powders, and exhibited advantageous properties as solid fuels that are often stored outdoors, with low COD of the wastewater discharged when stored outdoors.
[0150] Furthermore, the solid fuels of Examples d1 to d4 were also excellent in physical properties such as HGI, mechanical durability (DU), pH after immersion in water, and ball mill crushability.
[0151] <Example e: A mixture of larch, spruce and birch> In Examples e1 to e3 and Comparative Example e2 (PBT), a mixture of 50 wt% larch, 45 wt% spruce, and 5 wt% birch was used as the raw biomass, which was molded into pellets with a diameter of 8 mm in the molding process and heated to the heating temperature listed in Table 1B. The properties of the biomass solid fuel (Examples e1 to e3, Comparative Example e2) obtained after the heating process were measured by the above-mentioned method. In Comparative Example e1 (WP), the properties were measured using the same raw materials as Examples e1 to e3 and Comparative Example e2, except that the heating process was not performed. Since the moisture after immersion in water is after immersion for 168 hours, it is considered that the moisture in the solid fuel has substantially reached equilibrium. In Comparative Example e1, the pellets collapsed immediately after immersion in water, and it was not possible to measure each property. The results are shown in Tables 1B and 2.
[0152] The maximum temperature reached in the self-heating test for Comparative Example e2 (PBT) was 200°C. In contrast, the solid fuels of Examples e1 to e3 had low maximum temperatures reached in the self-heating test, indicating ease of transportation and storage. The results in Tables 1B and 2 indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature reached in the self-heating test.
[0153] Comparative Example e1 (WP) was unable to maintain its pellet shape and collapsed after immersion in water (168 hours) as described above. In contrast, the solid fuels of Examples e1 to e3 did not collapse when immersed in water, maintained the connections or adhesion between the biomass powders, and exhibited advantageous properties as solid fuels that are often stored outdoors, with low COD in the wastewater.
[0154] Furthermore, the solid fuels of Examples e1 to e3 were also excellent in physical properties such as HGI, mechanical durability (DU), pH after immersion in water, and ball mill crushability.
[0155] <Example f: A mixture of spruce, pine and fir> In Examples f1 to f6 and Comparative Example f2 (PBT), a mixture of 30 wt% spruce, 45 wt% pine, and 25 wt% fir was used as the raw biomass, which was molded into pellets with a diameter of 6 mm in the molding process and heated to the heating temperature listed in Table 3A. The properties of the biomass solid fuel (Examples f1 to f6, Comparative Example f2) obtained after the heating process were measured by the above-mentioned method. In Comparative Example f1 (WP), the properties were measured using the same raw materials as Examples f1 to f6 and Comparative Example f2, except that the heating process was not performed. Since the moisture after immersion in water is after immersion for 168 hours, it is considered that the moisture in the solid fuel has substantially reached equilibrium. In Comparative Example f1, the pellets collapsed immediately after immersion in water, and it was not possible to measure each property. The results are shown in Tables 3A and 3B.
[0156] The maximum temperature reached in the self-heating test for Comparative Example f2 (PBT) was 200°C. In contrast, the solid fuels of Examples f1 to f6 had low maximum temperatures reached in the self-heating test, indicating ease of transportation and storage. The results of Tables 3A and 3B indicate that the greater the volatile content (dry ash-free basis) of the solid fuel (PBT), the lower the maximum temperature reached in the self-heating test.
[0157] Comparative Example f1 (WP) was unable to maintain its pellet shape and collapsed after immersion in water (168 hours) as described above. In contrast, the solid fuels of Examples f1 to f6 did not collapse when immersed in water, and the connections or adhesion between the biomass powders were maintained. The COD of the wastewater discharged when stored outdoors was low, and these solid fuels exhibited advantageous properties as solid fuels that are often stored outdoors.
[0158] Furthermore, the solid fuels of Examples f1 to f6 were also excellent in physical properties such as HGI, mechanical durability (DU), pH after immersion in water, and ball mill crushability.
[0159] [Table 1A]
[0160] [Table 1B]
[0161] [Table 2]
[0162] [Table 3]
[0163] <Relationship between heating temperature during production of solid fuel and self-heating property> FIG. 1 shows the relationship between the solid temperature of the solid fuel and the maximum temperature in a wire basket test (same as the self-heating test described above) for Example a1, Example a3, Comparative Example a2, and Comparative Example a3 of the above Example a (rubber wood was used as the raw material). The maximum temperatures reached in Examples a1 and a3 were less than 200°C, but the temperatures rose to 200°C or higher in Comparative Examples a2 and a3. To study in more detail the relationship between the heating temperature of the solid fuel and the self-heating property, the inventors carried out the following measurements using the solid fuels produced in Examples a1, a3, Comparative Example a2, and Comparative Example a3.
[0164] (BET specific surface area) The relationship between the solid temperature and the BET specific surface area of the solid fuels of the above Examples a1, a3, and Comparative Examples a2 and a3 is shown in Figure 2. As the solid temperature increased, the BET specific surface area increased, and it was considered that as the temperature increased, pyrolysis progressed and the volatile content decreased (see Table 1A), and pores developed on the pellet surface, making it porous.
[0165] (Evolved gas analysis) Furthermore, the generated gas of the solid fuel was measured. For the generated gas analysis, the sample was filled in a 500mL glass wide-mouth bottle to 95% capacity and sealed with a silicone rubber stopper with a septum. The bottle was placed in a thermostatic chamber at 40℃ and 55% RH, and the generated gas (H2, O2, N2, CO, CH4, CO2) was analyzed by gas chromatography after one day. The relationship between the solid temperature and the O2, CO, and CO2 concentrations is shown in Figures 3A, 3B, and 3C, respectively. As the solid temperature increased, the O2 concentration decreased, confirming that the amount of O2 adsorbed on the surface of the solid fuel increased (Figure 3A). On the other hand, as the solid temperature increased, the CO and CO2 concentrations increased, suggesting that the adsorbed O2 caused an oxidation reaction (exothermic reaction) to proceed (Figures 3B and 3C).
[0166] Similarly, the solid fuels of Examples d2, d3, and Comparative Example d2 (the raw material was radiata pine) were also analyzed. The relationship between the solid temperature, the maximum temperature reached in the self-heating test, the BET specific surface area, and the O2 concentration determined by the evolved gas analysis is shown in Table 4. When the raw material was radiata pine, it was shown that there was a similar relationship between the solid temperature, the BET specific surface area, and the O2 concentration determined by the evolved gas analysis.
[0167] [Table 4]
[0168] From the results of Figures 1 to 3C and Table 4, the following reaction mechanism is considered for the relationship between the solid temperature of the solid fuel and the self-heating property. First, when the heating temperature during the production of the solid fuel increases, the volatile content decreases, the pellet surface becomes porous, and the BET specific surface area increases. This increases the amount of O2 adsorbed on the surface of the solid fuel, and the oxidation reaction (exothermic reaction) progresses. Therefore, it is presumed that when the solid temperature exceeds a certain temperature, the amount of heat stored exceeds the amount of heat released, and the self-heating property becomes 200°C or more.
[0169] <Ignitability> Furthermore, the present inventors investigated the thermal properties of the biomass solid fuel of the present invention and a solid fuel obtained through a process of steam explosion of biomass as described in Patent Document 1, and found that the biomass solid fuel of the present invention has excellent ignition properties. The biomass solid fuels used in the ignition property test are as follows.
[0170] Example a11: A solid fuel (PBT) obtained in the same manner as Example a1, except that rubber wood was used as the raw material, and the rubber wood was molded into pellets with a diameter of 8 mm in the molding process, and then heated to a target temperature of 250°C in the subsequent heating process. Example b3: Solid fuel (PBT) obtained in Example b3 above using acacia as the raw material Example c3: Solid fuel (PBT) obtained in Example c3 above using Dipterocarpaceae tree species as raw material Comparative Example q: A mixture of coniferous and broad-leaved trees is used as raw biomass, and the mixture is steam exploded to form a mass, which is then heated at 250°C to obtain a solid fuel q (obtained by the manufacturing method described in Patent Document 1).
[0171] Thermogravimetry (TG) and differential thermal analysis (DTA) were carried out for the above-mentioned Examples a11, b3, and c3, and Comparative Example q. The measurement methods for TG and DTA are as follows.
[0172] (TG and DTA) TG and DTA were measured using a Hitachi High-Tech Science STA7300 differential thermal and thermogravimetric simultaneous analyzer. 5 mg of a sample whose particle size was adjusted to 45-90 μm using a cutter mill was heated to 600°C at a heating rate of 5°C / min in the above-mentioned device while flowing 4 vol.% oxygen-nitrogen mixed gas at 200 cc / min, and held at that temperature for 60 min.
[0173] The results are shown in FIGS. 12 and 13. From the TG results, since the weight loss of Comparative Example q is slow, it can be said that the volatile content is less and the flammability is lower compared to Examples a11, b3, and c3. Also, from the DTA results, it can be said that in Comparative Example q, the heat generation occurs from the high-temperature side compared to Examples a11, b3, and c3, and the flammability is low. The reason is presumed that in Comparative Example q, the biomass solid fuel is obtained through the steps of pulverizing and drying the biomass, steam explosion, molding, and heating in this order, but during the steam explosion, the organic components float to the surface of the biomass powder and volatilize during the subsequent heating (carbonization). On the other hand, in PBTs such as Example a11, Example b3, and Example c3, it is presumed that the residual amount of volatile matter is large because they do not go through the explosion process.
[0174] Therefore, since the biomass solid fuel of the present invention does not include the step of steam explosion, in addition to being able to suppress the cost compared to Comparative Example q, it is considered to have excellent flammability.
[0175] Also, for the terpenes that form the solid cross-linking of PBT, the residual amount increases for the same reason, and a stronger solid cross-linking can be obtained. Therefore, it is presumed that PBT is superior in strength and water resistance compared to Comparative Example q.
[0176] <FT-IR Analysis of PBT and WP> FIGS. 5 to 9 are diagrams showing the results of FT-IR analysis of the biomass solid fuel r (solid fuel (PBT) obtained by heating the pelletized product after pulverization at 250 ° C.) obtained by the same method as Example b3 above using European red pine as the raw material. Also shown is the material obtained by pulverizing the same raw material and not heating it after molding (WP). In both the outer surface of the pellet (FIG. 5) and the center of the cross-section (FIG. 6), the amount of COOH groups is WP > PBT, and the amount of C = C bonds is PBT > WP. Also, the elution amount of COOH groups into the acetone extract (FIG. 7) is WP > PBT, indicating that PBT has fewer hydrophilic COOH groups. Furthermore, in the solid after acetone extraction (FIG. 8), PBT has more C = C bonds than WP. Therefore, it can be seen that PBT is superior in water resistance.
[0177] Figure 9 shows the results of GC-MS analysis of the acetone extract. The same solid fuels r(PBT) as in FIGS. 5 to 8 above and the unheated ones (WP) were used. As shown in FIG. 9, in PBT, the elution amount of abietic acid, which is a kind of terpene, into acetone is less than that of WP. After heating, abietic acid melts to form a liquid cross-link, and then it is considered that a solid cross-link is formed by the volatilization of abietic acid and the like. Since the biomass solid fuel of the present invention is also PBT obtained by molding and heating biomass powder, it is presumed that PBT has excellent water resistance by the same mechanism as the biomass solid fuel r.
[0178] <Water absorption distribution of PBT and PAT> Furthermore, in order to compare the water resistance of PAT and PBT, the present inventors examined the distribution of sodium after water absorption of these biomass solid fuels using saline water. As a sample of PAT, a solid fuel obtained by heating raw European larch at 250 ° C. and then molding it into pellets with a diameter of 6 mm was used. As a sample of PBT, a solid fuel obtained by molding raw European larch into pellets with a diameter of 6 mm and then heating it at 250 ° C. was used. PBT and PAT were immersed in 0.9 wt% physiological saline for 5 days. As a result, as shown in FIG. 10, the pellet appearance was such that PBT retained its pellet shape (left in FIG. 10), while PAT largely disintegrated (right in FIG. 10). In addition, the cross-sections of PAT and PBT were subjected to EPMA (Electron Probe MicroAnalyser) analysis before immersion in physiological saline and after immersion in 0.9 wt% physiological saline for 5 days, respectively, and the Na distributions were compared. The Na distribution was such that in PBT, it remained on the pellet surface and did not penetrate into the interior, whereas in PAT, it was widely distributed even inside (see FIG. 11). This means that less saline water penetrated into PBT than into PAT. From this result as well, in PBT, the pyrolyzate of the extraction component solid-cross-linked the gaps between adjacent biomass powders, making it hydrophobic and preventing water from entering, whereas in PAT, water could enter the gaps between the biomass powders, so water penetrated to the inside of the pellet, expanding the gaps between the biomass powders and resulting in disintegration.
Claims
1. The connection or adhesion between the biomass powders is maintained, The maximum temperature reached in the self-heating test based on the "United Nations: Recommendations on the Transport of Dangerous Goods: Manual of Tests and Criteria: 5th Edition: Self-heating Test" is less than 200°C, and A biomass solid fuel that satisfies any one of the following conditions (a1) to (f1): Condition (a1): The raw material of the biomass powder contains rubber wood, the content of rubber wood in the raw material is 100 wt%, and the volatile matter on an anhydrous ashless basis of the biomass solid fuel is 74.0 wt% or more; Condition (d1): The raw material of the biomass powder contains radiata pine, the content of radiata pine in the raw material is 100 wt%, and the volatile matter on an anhydrous ash-free basis of the biomass solid fuel is 77.5 wt% or more; Condition (e1): The raw material of the biomass powder contains a mixture of larch, spruce, and birch, the content of the mixture of larch, spruce, and birch in the raw material is 100 wt %, the weight ratio of larch:spruce:birch is 30-70:25-65:0-25, and the volatile content on an anhydrous ash-free basis of the biomass solid fuel is 71.0 wt % or more; Condition (f1): The raw material of the biomass powder contains a mixture of spruce, pine and fir, the content of the mixture of spruce, pine and fir in the raw material is 100 wt%, the weight ratio of spruce:pine:fir is 20-40:30-60:10-40, and the volatile matter on an anhydrous ash-free basis of the biomass solid fuel is 74.3 wt% or more.
2. 2. The biomass solid fuel according to claim 1, wherein the solid fuel has a dry ashless volatile content of 95.0 wt % or less and a fuel ratio of 0.10 to 0.
45.
3. The biomass solid fuel according to claim 1 or claim 2, wherein the connection or adhesion between the biomass powders is maintained after immersion in water.
4. The biomass solid fuel according to any one of claims 1 to 3, which satisfies any one of the following conditions (a2) to (f2): Condition (a2): The condition (a1) is satisfied, and the fuel ratio of the biomass solid fuel is 0.37 or less; Condition (d2): The condition (d1) is satisfied, and the fuel ratio of the biomass solid fuel is 0.295 or less; Condition (e2): The condition (e1) is satisfied, and the fuel ratio of the biomass solid fuel is 0.405 or less; Condition (f2): The condition (f1) is satisfied, and the fuel ratio of the biomass solid fuel is 0.34 or less.
5. The biomass powder is molded into a lump-shaped product, and the lump-shaped product is heated in a heating step. The biomass solid fuel according to any one of claims 1 to 4, which satisfies any one of the following conditions (a3) to (f3): Condition (a3): The condition (a1) is satisfied, and the heating temperature in the heating step is 170 to 254° C.; Condition (d3): The condition (d1) is satisfied, and the heating temperature in the heating step is 170 to 274° C.; Condition (e3): The condition (e1) is satisfied, and the heating temperature in the heating step is 170 to 289° C.; Condition (f3): The condition (f1) is satisfied, and the heating temperature in the heating step is 170 to 279°C.
Citation Information
Patent Citations
Method for manufacturing solid fuel, and solid fuel
JP2016193958A
Biomass solid fuel
WO2014087949A1
Solid biomass fuel
WO2016056608A1
Cooling apparatus for carbonized biomass
WO2017175737A1